Structures of care and credibility: Emotional abuse, institutional blind spots, and the gendered recognition of care - Vaughan, Ira Parker (The Australian journal of anthropology, 2025)
This article presents a fine-grained ethnographic case study of emotional abuse and child neglect within an intimate partner relationship in contemporary Australia, foregrounding the experience of a male primary caregiver whose distress remained institutionally illegible. Based on over 1500 pages of fieldnotes and presented with all names anonymised for ethical and protective reasons, the case offers an analytic entry point into the intersections of personhood, gendered care, narrative self-fashioning, and the limits of institutional response. The analysis develops a conceptual synthesis examining how lives become recognisable or remain invisible, how harm accrues through slow and cumulative events, and how gendered assumptions structure the moral economy of suffering. It explores why help-seeking by men in contexts of non-physical abuse is often redirected, minimised, or pathologised. The article argues that normative scripts of motherhood, legal frameworks for adjudicating “the child's best interest,” and the epistemological preferences of quantitative research together obscure forms of harm that are relational, ambiguous, and emotionally corrosive. Rather than offering prescriptive solutions, the case calls for the development of more inclusive frameworks that do not simply invert gender norms but challenge the assumptions underpinning institutional recognition itself. It contributes to ongoing debates about caregiving, gender, and vulnerability by demonstrating how anthropological approaches—especially ethnographic and interpretive methods—can expose subtle but consequential asymmetries in how care and harm are recognised, narrated, and acted upon.